-2(5f-2)=-10f+4

Simple and best practice solution for -2(5f-2)=-10f+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5f-2)=-10f+4 equation:

Simplifying
-2(5f + -2) = -10f + 4

Reorder the terms:
-2(-2 + 5f) = -10f + 4
(-2 * -2 + 5f * -2) = -10f + 4
(4 + -10f) = -10f + 4

Reorder the terms:
4 + -10f = 4 + -10f

Add '-4' to each side of the equation.
4 + -4 + -10f = 4 + -4 + -10f

Combine like terms: 4 + -4 = 0
0 + -10f = 4 + -4 + -10f
-10f = 4 + -4 + -10f

Combine like terms: 4 + -4 = 0
-10f = 0 + -10f
-10f = -10f

Add '10f' to each side of the equation.
-10f + 10f = -10f + 10f

Combine like terms: -10f + 10f = 0
0 = -10f + 10f

Combine like terms: -10f + 10f = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.`